Phosphate removal from aqueous solutions using a hybrid fibrous exchanger containing hydrated ferric oxide nanoparticles - Guaya Caraguay, D. (2015)
This study presents the evaluation of a fibrous ion exchanger impregnated with nanoparticles of hydrated ferric oxide (HFO) as a selective sorbent for phosphate. The hybrid impregnated anion exchanger (FIBAN-As) combines the durability and mechanical strength of a polymeric weak base anion exchange resin with the high sorption affinity of HFO towards phosphate species. The phosphate loading capacity at the common pH of waste waters treatment plant secondary effluents was 162 12 mg PO4 3-/g sorbent. Dynamic experiments were carried out and data obtained was fitted to fixed-bed sorption models. The theoretical sorption capacities reported by the Thomas model were in good agreement to the breakthrough experimental capacities determined from the sorption data. The sorption capacity decreased in multicomponent system due to the faster ion exchange of competing anions compared to phosphate ions. The loaded FIBAN-As was efficiently regenerated by using a sodium hydroxide solution, reporting up to 90% of recovery. Finally, reuse of FIBAN-As was evaluated in three successively sorption-desorption cycles by using two regeneration solutions. A sorption capacity reduction of 23% and 30% was observed for acid and alkaline solutions, respectively after the third cycle.